SIMULATION AND EXPERIMENTAL RESEARCH OF CLAW POLE MACHINE WITH A HYBRID EXCITATION AND LAMINATED ROTOR CORE - Wardach, Marcin; Prajzendanc, Paweł; Cierzniewski, Kamil; Cichowicz, Michał; Pacholski, Szymon; Wiszniewski, Mikołaj; Baradziej, Krzysztof; Osipowicz, Szymon (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
This paper presents the design and research results of a claw pole machine with hybrid excitation. This machine is excited by permanent magnets and an electromagnetic coil. Both excitation sources are located in the rotor of the machine. Additionally, the rotor is made of a laminated core. This approach facilitates the process of its construction and enables the implementation of even very complicated structure of the rotor, which would be difficult in case of making the rotor from a one piece of material. This paper presents the construction as well as the results of simulation and experimental tests of the machine prototype. The tests showed that the proposed machine has the ability to adjust the voltage in a wide range. Such as a feature could be used, for example, to increase the speed of motor operation in case of an electric vehicle application, but also to regulate the voltage in wind turbines which generators operate at varying rotor speeds resulting from changing wind speed.